2020
DOI: 10.1038/s41598-020-75260-w
|View full text |Cite
|
Sign up to set email alerts
|

Title: Cytokine release syndrome is not usually caused by secondary hemophagocytic lymphohistiocytosis in a cohort of 19 critically ill COVID-19 patients

Abstract: Severe COVID-19 associated respiratory failure, poses the one challenge of our days. Assessment and treatment of COVID-19 associated hyperinflammation may be key to improve outcomes. It was speculated that in subgroups of patients secondary hemophagocytic lymphohistiocytosis (sHLH) or cytokine release syndrome (CRS) with features of macrophage activation syndrome might drive severe disease trajectories. If confirmed, profound immunosuppressive therapy would be a rationale treatment approach. Over a median obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 51 publications
(71 reference statements)
0
19
1
1
Order By: Relevance
“…Increased levels in AST and ALT in COVID-19 are associated with the need for escalated care and higher rate of mortality [ 33 ]. Elevated ferritin is indicative of inflammation and cytokine storm, amongst others [ 34 ]. Lactate dehydrogenase is a marker of cell death and multi-organ failure [ 35 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels in AST and ALT in COVID-19 are associated with the need for escalated care and higher rate of mortality [ 33 ]. Elevated ferritin is indicative of inflammation and cytokine storm, amongst others [ 34 ]. Lactate dehydrogenase is a marker of cell death and multi-organ failure [ 35 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…At least 5 out of 8 symptoms (fever, splenomegaly, bicytopenia, hypertriglyceridemia and/or hypofibrinogenemia and hemophagocytosis, low/absent NK activity, hyperferritinemia, and high levels of sIL-2R/sCD25) are required to make a diagnosis according to the HLH-2004 criteria, of which only 6 are commonly available in clinical practice [ 158 ]. Meanwhile, an independent study of 19 severe COVID-19 cases with symptoms of hyperinflammation (neutrophil/lymphocyte ratio > 3.5) found that none of the patients met more than three HLH-2004 criteria [ 159 ]. For HLH/CSS verification and COVID-19 [ 160 ], the modified HLH-2009 criteria can be used.…”
Section: Systemic Reactions In Covid-19mentioning
confidence: 99%
“…This is evident in COVID-19 patients, where although an excessive cytokine reaction is evident, many of them do not fulfill the HLH criteria. A prospective study by Lorenz et al assessed HScores and a modified HLH-2004 criterion in 19 severe COVID-19 patients admitted to ICU, found a median HScore of 122, in the absence of confirmed presence of hemophagocytosis on bone marrow aspirate and a median HScore of 157, if assumed positive bone marrow aspirate criterion [172]. Notably, Prilutskiy et al performed autopsies on four confirmed COVID-19 patients which showed evidence of hemophagocytosis within pulmonary hilar/mediastinal lymph nodes but none of these patients showed hemophagocytosis in the bone marrow [173].…”
Section: Covid-19: Secondary Hlh Sepsis or Hlh-sepsis Overlap?mentioning
confidence: 99%
“…Notably, Prilutskiy et al performed autopsies on four confirmed COVID-19 patients which showed evidence of hemophagocytosis within pulmonary hilar/mediastinal lymph nodes but none of these patients showed hemophagocytosis in the bone marrow [173]. Of the 19 patients studied by Lorenz et al, only one patient reached a threshold >169 in the absence of the bone marrow aspirate criterion and six patients reached a threshold >169 if the bone marrow aspirate criterion was assumed positive [172]. Clark et al retrospectively reviewed 152 patients with polymerase chain reaction confirmed COVID-19 patients and demonstrated a median HScore of 52, with the majority of patients not reaching sufficient thresholds for an HLH diagnosis, although notably, many variables were missing including 46 patients who did not have ferritin levels and no patients having bone marrow biopsies collected [174].…”
Section: Covid-19: Secondary Hlh Sepsis or Hlh-sepsis Overlap?mentioning
confidence: 99%